2023
DOI: 10.3390/ani13030408
|View full text |Cite
|
Sign up to set email alerts
|

Donkey Heart Rate and Heart Rate Variability: A Scoping Review

Abstract: Heart rate (HR) and heart rate variability (HRV) are commonly used physiological measures in animals. While several studies exist on horse HRV, less information is available for donkeys. This scoping review aims to understand the extent and type of published evidence on donkey HR and HRV, their clinical and research applications, the devices used, and the analysis performed. Only quantitative primary studies published in English were considered. Four different databases were queried through the Web of Science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…As for HRV analysis, the only parameter that varied significantly when comparing the (+) and (−) tests and their respective phases (pre, test, and post) was rMSSD, a parameter reflecting short-term changes in HRV due mainly to parasympathetic nervous system activity [34,51]. rMSSD was significantly lower in the 'post' (−) test phase than in both the 'pre' (−) test/(−) 'test' phases, and the 'post' (+) test phase.…”
Section: Hrv Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…As for HRV analysis, the only parameter that varied significantly when comparing the (+) and (−) tests and their respective phases (pre, test, and post) was rMSSD, a parameter reflecting short-term changes in HRV due mainly to parasympathetic nervous system activity [34,51]. rMSSD was significantly lower in the 'post' (−) test phase than in both the 'pre' (−) test/(−) 'test' phases, and the 'post' (+) test phase.…”
Section: Hrv Analysismentioning
confidence: 99%
“…On the contrary, based on what was reported by other authors, ultra-short segments of one minute were considered [33,84]. Other unresolved issues concerning the analysis of HRV in donkeys, which is still in its infancy, were previously discussed in a scoping review on HR and HRV in donkeys [34]. This review also revealed that only two other studies have so far analysed HRV in donkeys [35,36], which makes our results difficult to compare and, thus, need to be interpreted with caution.…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 1 more Smart Citation